Gene Composition as a Potential Barrier to Large Recombinations in the Bacterial Pathogen Klebsiella pneumoniae. (2nd November 2019) - Comandatore, Francesco; Sassera, Davide; Bayliss, Sion C; Scaltriti, Erika; Gaiarsa, Stefano; Cao, Xiaoli; Gales, Ana C; Saito, Ryoichi; Pongolini, Stefano; Brisse, Sylvain; Feil, Edward J; Bandi, Claudio
Abstract: Klebsiella pneumoniae (Kp) is one of the most important nosocomial pathogens worldwide, able to cause multiorgan infections and hospital outbreaks. One of the most widely disseminated lineage of Kp is the clonal group 258 (CG258), which includes the highly resistant "high-risk" sequence types ST258 and ST11. Genomic investigations revealed that very large recombination events have occurred during the emergence of Kp lineages. A striking example is provided by ST258, which has undergone a recombination event that replaced over 1 Mb of the genome with DNA from an unrelated Kp donor. Although several examples of this phenomenon have been documented in Kp and other bacterial species, the significance of these very large recombination events for the emergence of either hypervirulent or resistant clones remains unclear. Here, we present an analysis of 834 Kp genomes that provides data on the frequency of these very large recombination events (defined as those involving >100 kb), their distribution within the genome, and the dynamics of gene flow within the Kp population. We note that very large recombination events occur frequently, and in multiple lineages, and that the majority of recombinational exchanges are clustered within two overlapping genomic regions, which have been involved by recombination events with different frequencies. Our results also indicate that certain lineages are more likely to act as donors to CG258. Furthermore, comparison of gene content in CG258 and non-CG258 strains agrees with this pattern, suggesting that the success of a large recombination depends on gene composition in the exchanged genomic portion.